2011
DOI: 10.1007/s00264-011-1373-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of total knee arthroplasty following high tibial osteotomy according to Wagner

Abstract: Purpose There is relatively little information available about the long-term results of total knee arthroplasty (TKA) following high tibial osteotomy. The aim of our study was to share our experiences and long-term results of TKA after a previous closing wedge high tibial osteotomy according to Wagner. Methods In a retrospective study we identified 48 consecutive patients who had undergone TKA after a previous closing wedge high tibial osteotomy according to Wagner with a follow-up of over ten years. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
1
22
0
3
Order By: Relevance
“…They also found use of stemmed implants similar to that in our study. Some independent studies with small numbers of patients have found equal outcome in TKA patients operated after HTO and in patients with a primary TKA regarding functional outcome and survival (Meding et al 2000), or functional measures only (Treuter et al 2012), whereas other studies have indicated more failures with higher reoperation rates (Parvizi et al 2004, Haslam et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…They also found use of stemmed implants similar to that in our study. Some independent studies with small numbers of patients have found equal outcome in TKA patients operated after HTO and in patients with a primary TKA regarding functional outcome and survival (Meding et al 2000), or functional measures only (Treuter et al 2012), whereas other studies have indicated more failures with higher reoperation rates (Parvizi et al 2004, Haslam et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The two most commonly performed HTO techniques for varus osteoarthritis are medial opening wedge HTO and lateral closing wedge HTO. Closing wedge HTO has a long history of use in cases of varus osteoarthritis and the majority of studies of results of TKA after HTO focus on lateral closing wedge osteotomies [2,20]. Frequently reported problems are related to previous surgery and consist of hardware removal, joint exposure, dealing with tibial deformities due to the previous osteotomy and managing soft tissue mismatches.…”
Section: Introductionmentioning
confidence: 99%
“…Ameliyat esnasında, ameliyat öncesinde hesaplanmış olan varus deformitesinin düzeltilmesine çalışılır. [5][6][7] Varus deformitesinin miktarını saptamak amacıyla en sık başvurulan yöntem, ameliyat önce-si dönemde çekilen ortoröntgenogramlardır. [8] Ortoröntgenogramların, deformite miktarını tespit etmede çok başarılı bir yöntem olduğunu belirten pek çok çalışma vardır.…”
Section: Discussionunclassified